Determination of lead in air by electrothermal atomic absorption spectrometry - Stafilov, Trajče; Kovacevski, Zoran; Trajkovska, Magdalena (Macedonian Journal of Ecology and Environment, 1993)
In this article, different methods for lead determination in various inorganic and organic compounds in the air, by electrothermal atomic absorption spectrometry are presented. The most convenient method for lead determination in inorganic compounds is based on absorption of the air sample in HN03 solution; and alkyl lead was determined after adsorption of the air sample on active carbon or silica gel. The limit of detection of this method is 0.03 ng lead and the relative standard deviation is in the 3.8 - 8.5% range. Using this procedures, the determination of lead in the air, in the different places in Skopje, was accomplished.